Human Rights Challenges to European Migration Policy The REMAP Study - Bast, Jürgen (Schriften zum Migrationsrecht, 2022)
The EU has become a powerful player in the area of migration. As a result, European migration policies increasingly conflict with the EU's commitment to respect Human Rights. The book identifies the most pressing challenges, outlines the relevant legal standards, and provides recommendations for reform. Core issues are asylum seekers' access to protection in the EU, personal liberty and free movement of migrants, safeguarding the rule of law in immigration proceedings, the prohibition of discrimination on any ground, including immigration status, respecting the social and family ties of migrants, guaranteeing minimum social rights for irregular migrants, and the public and private infrastructure necessary for defending the Human Rights of migrants.